2014
DOI: 10.1177/1367006914527186
|View full text |Cite
|
Sign up to set email alerts
|

Reference control in the narratives of adult sign language learners

Abstract: Aims and Objectives: Learning to control reference in narratives is a major step in becoming a speaker of a second language, including a signed language. Previous research describes the pragmatic and cognitive mechanisms that are used for reference control and it is clear that differences are apparent between first and second language speakers. However, some debate exists about the reasons for second language learners' tendency for over-redundancy in reference forms especially in the use of pronouns. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 60 publications
2
17
1
5
Order By: Relevance
“…L2 learners of spoken languages tend to adopt a strategy of overproducing overt forms when marking reference in order to reduce ambiguity (Gullberg, 2006;Hendriks, 2003). Bel et al (2015) found that L2 learners of sign also used this over-redundancy strategy. They overused overt pronouns and underused null pronouns for maintaining reference, in comparison to native signers, although these group differences did not reach statistical significance.…”
Section: What Might Learners Of a Sign Language Find Challenging Withmentioning
confidence: 97%
See 1 more Smart Citation
“…L2 learners of spoken languages tend to adopt a strategy of overproducing overt forms when marking reference in order to reduce ambiguity (Gullberg, 2006;Hendriks, 2003). Bel et al (2015) found that L2 learners of sign also used this over-redundancy strategy. They overused overt pronouns and underused null pronouns for maintaining reference, in comparison to native signers, although these group differences did not reach statistical significance.…”
Section: What Might Learners Of a Sign Language Find Challenging Withmentioning
confidence: 97%
“…At a gross level, it has been argued that despite the modality difference between signed and spoken language, there is the opportunity of transfer from learners' spoken L1 to their new signed L2, both of abstract linguistic entities (e.g., pragmatic constraints on reference, Bel et al, 2015) and of gesture (Chen Pichler and Koulidobrova, 2016). Alongside transfer is the possible existence of language learning universals, i.e., factors that will influence L2 learning whatever the L1 or the new language being learned (Chen Pichler and Koulidobrova, 2016).…”
Section: What Might Learners Of a Sign Language Find Challenging Withmentioning
confidence: 99%
“…The relative overall similarity between the native signers and the L2 learners might be an indication that the different-modality L2 learners have more cognitive resources available than same-modality L2 learners (Emmorey et al, 2012) and are able to allocate them to target-like referent tracking. The findings from Morgan (2002), Reynolds (2016), and particularly from Bel et al (2015) of some over-explicitness, however, cast doubt on this explanation and makes it more likely that our findings reflect the proficiency level of our participants. Previous L2 research has found that over-explicitness does not occur until the intermediate stage of acquisition (Ahrenholz, 2005; Hickmann, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…In the first study to investigate cross-modal adult L2 reference tracking to date, Bel et al (2015) looked at reference control in proficient L2 signers of Catalan Sign Language, whose first languages were Catalan and Spanish. They found some evidence of referential over-specificity in the L2 signers’ overall use of pronouns: compared to the native signers, the L2 signers used a greater proportion of pronominal reference and a lower proportion of null reference.…”
Section: Learning To Track Referencementioning
confidence: 99%
“…English) on the language that has such a choice, as some of these studies have concluded. However, anaphoric forms have also been found to cause optionality in bilingual speakers of two typologically similar languages, not only in speakers of two null-subject languages (Bini, 1993;de Prada Pérez, 2009, 2015Lozano, 2006;Margaza & Bel, 2006;Mendes & Iribarren, 2007;Sorace et al, 2009), but also in speakers of two Germanic languages (Ellert, 2013;Juvonen, 1996), bimodal bilinguals (Bel, Ortells, & Morgan, 2014), and unimodal bilinguals (Chen Pichler & Koulidobrova, 2016).…”
Section: Is Indeterminacy In L1 Attrition Caused By Transfer or By Bimentioning
confidence: 99%